Contributions of the social and solidarity economy to the implementation of the sustainable development goals and the construction of evaluation indicators: The case of a settlement in Araraquara, Brazil - Morais, Leandro Pereira [UNESP]; Bacic, Miguel Juan (My University, 2020)
In Brazil, and in many other countries, the Social and Solidarity Economy (SSE) has been an innovative alternative for job and I income generation, and a solution to cope with social and labor inclusion, in the last two decades. It can also be considered a new, more humane and inclusive model of development. This fact contributes to improving the quality of life, both for people and their communities, especially those with social and economic disadvantages. This conclusion led the United Nations to recognize the SSE as one of the auxiliary contributions to fulfilling the Sustainable Development Goals (SDGs). This is because the SDGs integrate and merge the three dimensions of sustainable territorial development: economic, social and environmental. However, at present, we need conclusive quantitative and qualitative studies and methodologies to be able to “quantify” the effective contributions of the SSE to the SDGs. Thus, this article aims to use a real and innovative experience of municipal SSE, carried out in an area of high socioeconomic vulnerability (Monte Alegre Land Reform Settlement), in the Brazilian municipality of Araraquara (SP), to explain its effective contributions to achieving certain SDGs. With this study, which is still being carried out, we also intend to propose a set of indicators for SDGs 1, 2, 5, 11 and 12, which can be applied in the future, as well as to other SSE experiments.
Keywords: 2030 Agenda, Brazil; Ecosystem; Indicators; Settlements; Social and solidarity economy; Territorial development